2015
DOI: 10.1111/cup.12623
|View full text |Cite
|
Sign up to set email alerts
|

Expression of G1/S‐cyclins and cyclin‐dependent kinase inhibitors in actinic keratosis and squamous cell carcinoma

Abstract: Our results suggest different alterations for p16(INK4a) and p21(Cip1) (/Waf1) in AK, SCCIS and SCC. Immunostaining distribution showed closer correlation with the type of the lesion, whereas percentage of positive cells displayed better association with the SCC prognostic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…CDK4 is overexpressed in human cSCCs and is sufficient to induce epidermal tumorigenesis concomitant with oncogenic Ras expression [ 184 ]. In AKs and cSCCs, Cyclin D1 slightly increases ( Table 2 ) as previously described [ 162 ]. Manojlovic-Gacic and colleagues show that Cyclin D1 is more expressed in ISSCC compared to AKs and in poor-differentiated cSCC compared to well-differentiated cSCC.…”
Section: P16 Ink4a and Non-melanosupporting
confidence: 58%
See 1 more Smart Citation
“…CDK4 is overexpressed in human cSCCs and is sufficient to induce epidermal tumorigenesis concomitant with oncogenic Ras expression [ 184 ]. In AKs and cSCCs, Cyclin D1 slightly increases ( Table 2 ) as previously described [ 162 ]. Manojlovic-Gacic and colleagues show that Cyclin D1 is more expressed in ISSCC compared to AKs and in poor-differentiated cSCC compared to well-differentiated cSCC.…”
Section: P16 Ink4a and Non-melanosupporting
confidence: 58%
“…In BCC, 16 INK4a may also be inactivated apart from loss of heterozygosity, promoter hypermethylation, and/or mutations in the INK4a/ARF locus [ 161 ]. On the contrary, several immunohistochemical studies report an increased 16 INK4a expression in ISSCCs compared to AKs and in poor differentiated cSCC compared to well differentiated [ 157 , 159 , 162 , 163 , 164 ]. In premalignant AKs, 16 INK4a expression correlates with a functional pRb pathway, suggesting that upregulation is the result of senescence induction following stress stimuli [ 165 ].…”
Section: P16 Ink4a and Non-melanomentioning
confidence: 98%
“…The combination of high PHLDA1 and p53 staining appeared highly specific for invasive SCC compared to SK and VV. Low PHLDA1 and p53 staining demonstrated moderate sensitivity for VV in this small collection of cases, but a specific marker for VV was not apparent from the markers tested [40]. Although our sample size is limited and does not include in situ SCC cases, our findings provide some support for utilization of IHC when a superficial shave biopsy specimen prompts the differential diagnosis of invasive SCC, SK, and VV.…”
Section: Discussionmentioning
confidence: 65%
“…Mutations in the p53 gene have been found in a large percentage of human skin malignancies, which are not only involved in the malignant conversion of AK to cSCC but also useful as biomarkers for predicting skin cancer . Meanwhile, the immunostaining distribution of p16 INK4a and p21 Cip1/Waf1 were shown to be different in AK and cSCC . In 2014, Lambert S R et al performed genome‐wide microarray analysis and found that the MAPK pathway may be pivotal in the transition from AK to cSCC, thus representing a potential target for cSCC prevention.…”
Section: Introductionmentioning
confidence: 99%
“…8 Meanwhile, the immunostaining distribution of p16 INK4a and p21 Cip1/Waf1 were shown to be different in AK and cSCC. 9 In 2014, Lambert S R et al 10 performed genome-wide microarray analysis and found that the MAPK pathway may be pivotal in the transition from AK to cSCC, thus representing a potential target for cSCC prevention. Nevertheless, the most crucial genes responsible for the progression of AK to cSCC have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%